79 Tahun Negara Hukum: Refleksi Atas Upaya Mewujudkan Negara Hukum Pancasila Yang Melindungi Hak Asasi Manusia - Basuki, Udiyo; Kurnia, Kamal Fahmi (Universitas Sang Bumi Ruwa Jurai, 2025)
Exactly 79 years ago, on August 17, 1945, the independence of the Republic of Indonesia was proclaimed, and in its constitution, the 1945 Constitution, in the Body and Explanation it is emphasized that Indonesia is a state of law. In the Body there are also various provisions that regulate Human Rights. It is recognized that the state of law and human rights are issues that must be discussed in one breath, because there is no state of law without the recognition of human rights and the enforcement of human rights is an unbroken chain with the principles of democracy and the state of law.In the two main axes of the concept of the state of law, Recht Staat and the rule of law, which were both born and developed in Europe, Indonesia carries the concept of the Pancasila state of law. The Pancasila state of law is a concept of a state of law that is based on the noble views and philosophies of life of the Indonesian people from generation to generation. It is also a form of crystallization of views and philosophies of life that are full of noble ethical and moral values as stated in the 1945 Constitution. Recognition as a country of law demands the upholding and implementation of what is ideally organized by a country of law. So it will be studied how to realize a Pancasila country of law that protects Human Rights